Driven to fight, negotiating for survival: a history of female guerrillas in the Malayan Communist Party (1948-1989) - Tan, Wen Xuan (Nanyang Technological University, 2025)
This thesis analyses how the Malayan Communist Party (MCP)’s hierarchy, British and Malaysian laws have influenced the participation of female guerrillas in the Party from 1948 to 1989. Existing literature has mainly examined how dominant British, Malaysian and communist narratives have overlooked the women’s contributions to the MCP during the First and Second Malayan Emergency, and the female insurgents’ active resistance towards British, Malaysian and communist regulations in both insurgencies. However, disparities in party rankings, gender and race enabled these dominant narratives to overlook how their systems influenced the women’s implicit strategies in navigating their interests, neglecting how women shaped the trajectory of both insurgencies within British, Malaysian and communist regulations. Using Datta’s “situational agency”, Foucauldian and Levi’s microhistorical approaches, I examine how women implicitly navigated British, Malaysian and the MCP’s restrictions by reviewing memoirs, communist propaganda and British and Malaysian laws. By doing so, I argue that the Party’s rankings, British and Malaysian ordinances encouraged female guerrillas to negotiate their positions within existing regulations. By bridging top-down and bottom- up discourses, this thesis contributes to gender history in Malaysia and Southeast Asia by broadening the scope of female participation in political mobilisation during both insurgencies.